Holland Family : Another Kind of Eden - Book 12 - Burke, James Lee 1936- (New York : Simon & Schuster, 2021)
"New York Times bestselling author James Lee Burke brings readers a captivating tale of justice, love, brutality, and mysticism set in the turbulent 1960s"--
Keywords: Historical Fiction